ESRA19-0160 Pericapsular nerve group (PENG) block after total hip arthroplasty. A report of five cases. (30th August 2019) - Azpiazu, N; Perez, P; Taibo, JM; Ortega, U; Diez, E; Velasco, C
Abstract : Background and aims: Total hip arthroplasty (THA) generates significant postoperative pain that may be treated using nerve blocks. However, they usually have some limitations such as the quadriceps strength loss, thus delaying mobilization and early rehabilitation. We evaluate the effectiveness of the pericapsular nerve group (PENG) block, aiming a good analgesic quality along with the preservation of quadriceps strength. That way, we would be able to block branches of the femoral nerve, the obturator nerve and the accessory obturator nerve, which are responsible of the pain pathway from the hip joint. Methods: We have performed ultrasound-guided PENG block consecutively in five patients in the post-anesthesia care unit (PACU) after surgical intervention of THA. A 50 mm or 80 mm needle was inserted according to the anatomical characteristics of each patient, in plane with ultrasound beam. Following negative aspiration, 30 ml levobupivacaine 0.5% was infiltrated between the iliopubic eminence and the iliopsoas tendon. Opioid consumption was assessed during 12 hours after the block as primary outcome measure for pain. On the same period of time, we evaluated quadriceps strength by lifting the leg up to 15°. Results: There was no need for opioid consumption in four patients, while one required 6 mg IV Morphine. In addition, all patients could extent hip joints up to 15°. Conclusions: The PENG block could be a new technique for good quality sole sensory nerve block in THA surgery, without quadriceps motor blockade. A strong analgesia along with a decreasing risk of quadriceps muscle weakness would obviate delay in ambulation.